INTERPRETASI YUSUF AL-QARADAWI TERHADAP HADIS HISAB-RUKYAT (Studi Kritis Atas Karya Kaifa Nata’amalu ma’a as-Sunnah an-Nabawiyyah) - Mufid, Abdul (IAIN Kediri, 2020)
This paper aims to explore as far as possible the interpretation of Yusuf al-Qaradawi related to the hadith determination of the beginning of the lunar month which also contains the rites of the hadith rukyat. This kind of study is urgent to do, because besides being phenomenological, it also occurs at the level of social reality. The primary reference in this paper is the author's review of his work Kaifa Nata'amalu ma'a as-Sunnah an-Nabawiyyah and some of his other works. Meanwhile the secondary source is the writer who studies from other scholars. The results of the study showed that Yusuf al-Qaradawi placed himself in the middle position between hisab and rukyat. In other words, the results of Yusuf al-Qaradawi's reading of the hadith’s rukyat nuances show to prioritize the reckoning method of hilal visibility, not rukyat, nor hisab.Keywords: Interpretation, Yusuf al-Qaradawi, Hadith